Thinning of the Horcones inferior debris-covered glacier, derived from five ablation seasons by semi-continuous GNSS geodetic surveys (Mt. Aconcagua, Argentina) - Lenzano, Luis Eduardo (2016)
We report on ice movements changes in the Horcones Inferior Glacier (HIG), a major debris-covered glacier located in the southern sector of Mt. Aconcagua, Central Andes of Argentina. The HIG has been characterized by outstanding surge phenomena in the recent past, with the last episode registered in 2003. After a surge episode, the surface becomes highly unstable, with continuous ice degradation. We studied the response of the glacier surface in the post-surge stagnation period, based on six semi-continuous Global Navigation Satellite System (GNSS) stations distributed along the main axis of the glacier. Kinematic GNSS profiles were acquired over the surface, aiming to strengthen the GNSS measurements of elevation change. Our results show a horizontal surface displacement from 0.4 cmd-1 to 2.7 cmd-1, and a 0.8 cmd-1 mean elevation reduction during the 2009-2014 period. GNSS profiles also show a velocity increase, ranging from-1.1 cmd-1 in 2012 to-1.8 cmd-1 in 2013. Changing surface velocities in the HIG may be related to the presence of a thick debris cover, in combination with faster glacier degradation due to thickness loss after the 2003 surge, and glacier-climate interaction.